2019
DOI: 10.1017/s1463423619000215
|View full text |Cite
|
Sign up to set email alerts
|

Primary health care workers’ understanding and skills related to cervical cancer prevention in Sango PHC centre in south-western Nigeria: a qualitative study

Abstract: Aim: The study explored the knowledge and service delivery skills of primary health care (PHC) workers to conduct cervical cancer screening programmes in Sango primary health centre in Sango town, Ado-Odo Ota, Ogun State in Nigeria. Background: Cervical cancer is the second most common cancer affecting women. The prevention and control services in Nigeria are provided mainly at post-primary health facilities. Authorities have advocated the integration of cervical cancer prevention into r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 36 publications
(42 reference statements)
2
16
0
1
Order By: Relevance
“…More than half (55%) reported their rst sexual intercourse between the age of 15-19 years and the median age 16 years (IQR, [15][16][17][18]. Regarding age at rst pregnancy, the median was 17 years (IQR, [16][17][18][19] and more than half (55%) had their rst pregnancy at < 18 years.…”
Section: Participants' Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…More than half (55%) reported their rst sexual intercourse between the age of 15-19 years and the median age 16 years (IQR, [15][16][17][18]. Regarding age at rst pregnancy, the median was 17 years (IQR, [16][17][18][19] and more than half (55%) had their rst pregnancy at < 18 years.…”
Section: Participants' Characteristicsmentioning
confidence: 99%
“…However, the health providers' VIA screening skills have been shown to improve signi cantly over time with continuous exposure and practice (15). For example in Ghana, the health care providers who had been trained up to seven years with regular supervision maintained high visual inspection performance (16).…”
Section: Introductionmentioning
confidence: 99%
“…However, even with the simplest methods in place, health care providers still face challenges in service provision due to various factors. The factors that hinder screening have been classified into: the health care system and health care provider related [ 7 - 9 ]. According to two studies, inaccessibility to health care centres and the unavailability of quality services are hindrances to cervical cancer screening [ 8 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies showed that health care providers identified the following barriers in offering cervical cancer screening: insufficient screening centre/space and equipment at their working places, financial barriers for clients in those health care centres where screening is charged [ 7 , 8 , 12 , 15 - 17 ]. Furthermore, two studies conducted in Zimbabwe showed that lack of time dedicated to counselling and educating women on cervical cancer and staff shortages served as deterrents to screening [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation